The making of Southeast Asia international relations of a region - Acharya, Amitav (Cornell studies in political economy, 2012)
The idea of the 'nation' is a Western concept which has been applied to Southeast Asia. It is a project which has been in progress since the last century but is still incomplete. Various theoretical frameworks which are associated with nation and nation-building in the Southeast Asian region have been briefly dealt with. The book aims to examine the making of the nations in Southeast Asia using both historical and political science approaches. Concepts related to nation such as ethnicity, state, indigenism and citizenship have also been analysed in the Southeast Asian context. Specific examples of nation-building in five major Southeast Asian countries are presented. Problems and prospects of Southeast Asia's nation-building and citizenship building in the era of globalisation are also discussed